2021
DOI: 10.3390/gels7040200
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinization, Retrogradation and Gel Properties of Wheat Starch–Wheat Bran Arabinoxylan Complexes

Abstract: Gelatinization, retrogradation and gel properties of wheat starch–wheat bran arabinoxylan (WS–WBAX) complexes have been evaluated. The results of rapid viscosity analyzer (RVA), differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR) confirmed that WBAX samples with larger Mw and branching degree (HWBAX) significantly impeded gelatinization process of starch by effectively reducing the amount of water available for starch gelatinization. DSC analysis showed that both molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…At the same time, the order of G′ from all samples was PS-LKGM > PS > PS-MKGM > PS-HKGM. Similar phenomena were reported that at the same angular frequency starch gels with HWBAX (wheat bran arabinoxylan with a larger Mw and branching degree) revealed the smaller G′ compared to starch paste containing the same amount of LWBAX (wheat bran arabinoxylan lower Mw and branching degree) [ 16 ]. Moreover, the order of G″ from blends under the same time condition was as follows: PS-HKGM > PS-MKGM > PS-LKGM > PS.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…At the same time, the order of G′ from all samples was PS-LKGM > PS > PS-MKGM > PS-HKGM. Similar phenomena were reported that at the same angular frequency starch gels with HWBAX (wheat bran arabinoxylan with a larger Mw and branching degree) revealed the smaller G′ compared to starch paste containing the same amount of LWBAX (wheat bran arabinoxylan lower Mw and branching degree) [ 16 ]. Moreover, the order of G″ from blends under the same time condition was as follows: PS-HKGM > PS-MKGM > PS-LKGM > PS.…”
Section: Resultssupporting
confidence: 81%
“…Moreover, the molecular weight (Mw) of the polysaccharide also has an influence on the aging properties of starch. For the same polysaccharide, the larger the Mw, the more effective it was at restraining starch aging, such as wheat bran arabinoxylan [ 16 ], water-extractable arabinoxylan [ 17 ], corn fiber gum [ 18 ], dextran [ 19 ] and pectin [ 20 ]. By contrast, the smaller the Mw of the same polysaccharide, the more significant it was at inhibiting starch aging, including water-extractable arabinoxylan [ 17 ], inulin [ 21 ] and branched limit dextrins [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Retrogradation, gelatinization, gel rheology [ 44 ], solubility, cold swelling, water absorption [ 45 ], syneresis, viscosity, tackiness, and shear resistance [ 32 ] are functional properties that can be used to determine the structural and molecular distribution of amylose and amylopectin when they are subjected to various processing techniques and applications. In the presence of a specific quantity of moisture, the heat treatment action on amylose and amylopectin results in noticeable alterations to the structure of starch [ 46 , 47 ].…”
Section: Structure Of Starchmentioning
confidence: 99%
“…The gelatinisation properties of RS+MBC samples were determined by differential scanning calorimetry (DSC; DSC-214, Netzsch Co. Ltd., Germany) following a previous method (Yan et al, 2021). MBC (0.15 g, dry weight basis) was dissolved in distilled water (12 mL) with continuous magnetic stirring for 2 h at 25°C.…”
Section: Effect Of Mbc On Gelatinisation and Retrogradation Propertie...mentioning
confidence: 99%
“…Then, retrogradation enthalpy (ΔHR) was determined from the curves. The retrogradation percentage (R%) was calculated by dividing the ΔHR of the second heating run at 28 days by ΔHg in the first heating run (Temsiripong et al, 2005;Yan et al, 2021). Analyses were performed in triplicate.…”
Section: Effect Of Mbc On Gelatinisation and Retrogradation Propertie...mentioning
confidence: 99%